Advances in Electrospun Polymer-Based Nanofibers for Wound Healing: A Narrative Review - Imanto, Teguh; Zahra, Veirda (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Polymer-based nanofibers produced using electrospinning techniques have become a significant innovation in drug delivery systems, particularly in wound healing. The nanofiber structure, which resembles the extracellular matrix (ECM), provides an advantage in supporting tissue regeneration and drug release control, making it an effective solution for the treatment of acute and chronic wounds. The aim of this review is to analyze recent advancements in the use of polymer-based nanofibers for drug delivery in wound healing therapy. The method used is a systematic approach with modified PRISMA guidelines. Relevant literature was extracted from the ScienceDirect database using the keywords